An Analysis of Code Switching and Code-Mixing on Instagram Reels - Kamayana, I Gusti Nyoman Putra (Seminar Ilmiah Nasional Teknologi, Sains, dan Sosial Humaniora (SINTESA), 2024)
This study aims to analyze the code-switching and code-mixing found on content creator’s Instagram reels. The qualitative descriptive method is used in this study to analyze the data. The source of the data was Instagram reels by an Indonesian content creator. The sample of this study was a content creator, Gita Savitri Devi, well-known as Gita, with her Instagram account @gitasav. Data was collected from her video reels to conduct skin-care products. The theory of code-switching types by Myers-Scotton (1993) and code-mixing types by Muysken (2000) is used in this study. The result showed that two types of code-switching were found, namely inter-sentential with 5 data points and intra-sentential with 5 data points. All three types of code-mixing are found: alternation with 7 data points, insertion with 2 data points, and congruent lexicalization with 1 data point.